The Effect of Profitability, Leverage, Firm Size, and Liquidity on Firm Value in Indonesia Property Sector - Nur Afiqoh Sari; Armizha Rahmatika; Meilenia Rahma Salisa; Lina Nasehatun Nafidah (LifeSciFi, 2026)
The dynamics of the Indonesian property and real estate sector, which is highly influenced by macroeconomic conditions, particularly during the 2019–2024 period, covering the COVID-19 pandemic and the subsequent economic recovery phase. The objective of this study is to examine the effects of profitability, leverage policy, firm size, and liquidity on firm value. A quantitative approach is employed using multiple linear regression analysis based on secondary data obtained from Osiris and annual financial reports of companies listed on the Indonesia Stock Exchange (IDX), with a total of 180 observations. The results indicate that profitability has no significant effect on firm value, leverage has a positive and significant effect, while firm size and liquidity have significant negative effects on firm value. These findings suggest that investors place greater emphasis on capital structure and operational efficiency rather than short-term profitability in valuing property firms. In conclusion, firm value in this sector is more strongly influenced by leverage signaling and asset utilization efficiency than by net income performance. The implications of this study are that corporate managers should optimize financing strategies and asset management efficiency, while investors are encouraged to pay closer attention to capital structure and operational efficiency in making investment decisions.